The Influence of Avatar Personalization on Emotions in VR - Rivu Radiah; Daniel Roth; Florian Alt; Yomna Abdelrahman (Multimodal Technologies and Interaction, 2023)
In this paper, we investigate the impact of avatar personalization on perceived emotions. Avatar embodiment is a crucial aspect of collaborative and social virtual reality (VR) systems. Previous research found that avatar appearance impacts the acceptability of the virtual body and changes users’ behavior. While virtual embodiment has been extensively investigated, we know very little about how embodiment affects users’ experienced emotions. In a user study (N = 40), we applied an autobiographical recall method to evoke happiness and investigated the influence of different types of avatar embodiment (personalized same-gender, personalized opposite-gender, non-personalized same-gender, and non-personalized opposite-gender) on participants’ perceived emotion. We recorded both self-reported assessments and physiological data to observe participants’ emotional responses resulting from the emotions elicited by the use of different avatars. We found significant differences in happiness with the personalized same-gender avatar and the personalized opposite-gender avatar. We provide empirical evidence, demonstrating the influence of avatar personalization on emotions in VR. We conclude with recommendations for users and designers of virtual reality experiences.